HCI International 2015 - Posters' Extended Abstracts International Conference, HCI International 2015, Los Angeles, CA, USA, August 2-7, 2015. Proceedings, Part II - Stephanidis, Constantine (Communications in Computer and Information Science,, 2015)
This is the second volume of the two-volume set (CCIS 528 and CCIS 529) that contains extended abstracts of the posters presented during the 17th International Conference on Human-Computer Interaction, HCII 2015, held in Heraklion, Crete, Greece in August 2015. The total of 1462 papers and 246 posters  presented at the HCII 2015 conferences was carefully reviewed and selected from 4843 submissions. These papers address the latest research and development efforts and highlight the human aspects of design and use of computing systems. The papers thoroughly cover the entire field of human-computer interaction, addressing major advances in knowledge and effective use of computers in a variety of application areas. The papers included in this volume are organized in the following topical sections: mobile interaction and smart devices; social media; HCI in business and innovation; learning technologies; HCI in health; assistive technologies and environments; fitness and well-being applications; location and context awareness; urban interaction; automotive and aviation; design and user studies.